Politeness In Online Communication: Retailer-Client Interaction - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri; Omar, Siti Rohana (GIAP Journals, 2019)
Purpose of the study: The paper aims to unfold politeness in online communication among retailers and clients and debates some ways where cultural values of communication can be taught and thus re-learned. Methodology: The qualitative approach was adopted where discourse analysis method used to review and analyse the updates and comments from Facebook and WhatsApp of conveniently collected data for this study. Main Findings: The study suggest a deterioration of cultural values in communication is at an alarming level among retailers and clients in online communication. Applications of this study: The study will benefit online businesses. Area of studies include business management and communication. Other sub- areas include culture and ethic relations. Novelty/Originality of this study: The study is new to Malaysian business context where multi-racial and multilingual environment play significant roles.